A biosafety evaluation of synchrotron radiation X-ray to skin and bone marrow: single dose irradiation study of rats and macaques. (3rd June 2017) - Lu, Yifan; Tang, Guanghui; Lin, Hui; Lin, Xiaojie; Jiang, Lu; Yang, Guo-Yuan; Wang, Yongting
Abstract: Purpose: Very limited experimental data is available regarding the safe dosages related to synchrotron radiation (SR) procedures. We used young rats and macaques to address bone marrow and skin tolerance to various doses of synchrotron radiation. Methods: Rats were subjected to 0, 0.5, 2.5, 5, 25 or 100 Gy local SR X-ray irradiation at left hind limb. Rat blood samples were analyzed at 2–90 days after irradiation. The SR X-ray irradiated skin and tibia were sectioned for morphological examination. For non-human primate study, three male macaques were subjected to 0.5 or 2.5 Gy SR X-ray on crus. Skin responses of macaques were observed. Results: All rats that received SR X-ray irradiation doses greater than 2.5 Gy experienced hair loss and bone-growth inhibition, which were accompanied by decreased number of follicles, thickened epidermal layer, and decreased density of bone marrow cells ( p < 0.05). Macaque skin could tolerate 0.5 Gy SR X-ray but showed significant hair loss when the dose was raised above 2.5 Gy. Conclusion: The safety threshold doses of SR X-ray for rat skin, bone marrow and macaque skin are between 0.5 and 2.5 Gy. Our study provided essential information regarding the biosafety of SR X-ray irradiation.